2014
DOI: 10.1016/j.jnutbio.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of (−)-epicatechin on molecular modulators of skeletal muscle growth and differentiation

Abstract: Sarcopenia is a notable and debilitating age-associated condition. Flavonoids are known for their healthy effects and limited toxicity. The flavanol (−)-epicatechin (Epi) enhances exercise capacity in mice and Epi-rich cocoa improves skeletal muscle structure in heart failure patients. (−)-Epicatechin may thus, hold promise as treatment for sarcopenia. We examined changes in protein levels of molecular modulators of growth and differentiation in young vs. old, human and mouse skeletal muscle. We report the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
73
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 16 publications
5
73
1
Order By: Relevance
“…As being mentioned early, EC significantly reduced TG at a very low dose (1 mg/kg BW) , but not at a much higher dose (0.01 mol/kg BW). Incredibly wide range doses of EC, from 1 mg/kg BW to 3 g/kg BW , were found in the studies to investigate the cardiovascular benefits of EC. Nevertheless, most studies selected the physiological or near physiological doses, which fell in the range of 10–50 mg/kg BW.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As being mentioned early, EC significantly reduced TG at a very low dose (1 mg/kg BW) , but not at a much higher dose (0.01 mol/kg BW). Incredibly wide range doses of EC, from 1 mg/kg BW to 3 g/kg BW , were found in the studies to investigate the cardiovascular benefits of EC. Nevertheless, most studies selected the physiological or near physiological doses, which fell in the range of 10–50 mg/kg BW.…”
Section: Discussionmentioning
confidence: 57%
“…The molecular mechanisms are largely unknown. In one study to evaluate the effects of EC on a high‐fat diet induced rat model of cardiometabolic risk factors, EC was found to significantly reduce TG at a very lower dose (1 mg/kg BW) . Another study conducted by the same group confirmed that, when consuming two capsules of 25 mg EC twice a day orally, human subject with hypertriglyceridemia displayed a significantly drop of TG by 75 mg/dL.…”
Section: Discussionmentioning
confidence: 96%
“…Lee et al reported a dose-dependent effect of EC on the protein levels of MHC, MyoD and myogenin, and stimulation of promyogenic signaling pathways, p38 MAPK and Akt, in EC-treated C2C12 myoblasts [24]. In addition, Gutierrz-Salmean et al proved that EC treatment resulted in a significant increase in the levels of MEF2, Myf5, MyoD, and myogenin in the skeletal muscles of old EC-treated mice (25 months) and the muscle strength in human hands [25]. Experimental evidence found using HepG2 cells and C2C12 skeletal muscle myotubes demonstrated that FOXO transcription factors are sufficient for activating and increasing the levels of a MuRF1 promotor fragment, atrogin-1, and/or MuRF1 mRNA expression [26].…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we have tried to investigate the effect and molecular mechanism of EC as a compound for improving muscle differentiation. The positive role of EC in the regulation of muscle growth and differentiation has been previously referred by Ramirez-Sanchez group [13]. However, the molecular mechanism by which EC modulates myogenic differentiation was unclear.…”
Section: Discussionmentioning
confidence: 99%
“…EC significantly promotes osteogenic proliferation, differentiation and mineralization [12]. Furthermore, the treatment of EC enhances the level of myogenic genes, such as MEF2, Myf5 and MyoD in skeletal muscles of old mice, and one week treatment with EC in humans increased muscle strength in hands [13]. However, the detailed mechanism of the positive effect of EC on muscle growth has not been examined.…”
Section: Introductionmentioning
confidence: 99%